Pengaruh geographical inquiry terhadap kemampuan berpikir analitis siswa dalam mata pelajaran geografi kelas XI di MA AL UMM - Rimayanti, Ika Nova; Rosyida, Fatiya; Wagistina, Satti; Handoyo, Budi (Universitas Negeri Malang, 2023)
Geographical Inquiry is a mindset with which students can identify geographical phenomena through learning models to train students to think analytically. This research was conducted to know the effect of the geographical research learning model on analytical patterns. The research conducted is included in pseudo-experimental research with two classes, namely the experimental class and the control class, which is in accordance with the results of the UTS scores in the even semester. The subjects in this study were students of grade 11 Social Studies Department 1 as the control class and 11 Social Studies Department 2 as the experimental class at MA AL UMM. Data collection used by researchers is pre-test and post-test testing techniques. The resulting data can be analysed using an independent sample t-test. The results of the analysis obtained from the t-test show that the sig value (2-tailed) of the average Gain Score in the experimental class is 12 while in the control class it is 4.5 The difference in the average Gain Score between the experimental and control groups is 7.5 which means that everyone increase in variable X (geographical inquiry model), the value of variable Y (learning outcomes) will increase. So, the experimental class has a more excellent average than the control class, so Ho is rejected. It can be concluded that learning geographical inquiry has an effect on the geographical analytical thinking of Grade 11 social studies students at MA AL UMM. Geographical Inquiry merupakan pola pikir yang dengannya siswa dapat mengidentifikasi fenomena geografis melalui model pembelajaran sehingga dapat melatih siswa untuk berpikir analitis. Penelitian ini dilakukan dengan tujuan agar tahu akan pengaruh model pembelajaran penelitian geografi pada pola analitis. Penelitian yang dilakukan termasuk dalam penelitian eksperimen semu dengan dua kelas yaitu kelas eksperimen dan kelas kontrol yang sesuai dengan hasil nilai UTS pada semester genap. Subjek dalam penelitian ini yaitu siswa kelas 11 Jurusan IPS 1 sebagai kelas kontrol dan 11 Jurusan IPS 2 sebagai kelas eksperimen di MA AL UMM. Pengumpulan data yang digunakan oleh peneliti adalah teknik pre-test dan post-test testing. Data yang dihasilkan dapat dianalisis menggunakan independent sample t-test. Hasil analisis yang didapatkan dari uji-t menunjukkan bahwa nilai sig (2-tailed) hasil rata-rata Gain Score pada kelas eksperimen adalah 12 sedangkan pada kelas kontrol sebesar 4,5 Selisih rata-rata Gain Score antara kelompok eksperimen dan kontrol sebesar 7,5 yang artinya setiap kenaikan satu variabel X (model geographical inquiry) maka nilai variabel Y (hasil belajar) akan naik. Sehingga kelas eksperimen memiliki rata-rata lebih besar dari kelas kontrol, sehingga Ho ditolak. Dapat disimpulkan bahwa pembelajaran penelitian geografi berpengaruh terhadap pemikiran analitik geografis siswa Kelas 11 Jurusan IPS di MA AL UMM.